Ang Balager at ang Maqueda sa mga alimpuyo ng isla - Breis, Niles Jordan (2020)
Accessed online through this link: https://journals.upd.edu.ph/index.php/Lirip/article/view/8111/7081
Keywords: Books -- Reviews; Catanduanes; Barrameda, Emmanuel T; Arcilla, Napoleon III